WHAT MAKES INDONESIA'S SUSTAINABLE INVESTMENT BETTER THAN SHARIAH AND LIQUID? - Indra Gunawan; Muhammad Firdaus; Hermanto Siregar; Mulya E. Siregar (School of Business, Bogor Agricultural University (SB-IPB), 2021)
This study aimed to compare the performance of SRI-KEHATI, lq45, and JII weekly data set from 2009 to 2020, covering 100 companies' stocks as members of the indices. Data were standardized within index weighting, followed by non-parametric methods as they were not as susceptible to outliers as the parametric tests were. The performance evaluation used both Kruskal-Wallis and Mann-Whitney U tests. The result showed that SRI- KEHATI had the largest average risk and returns, among others, supported by the fact that investors will choose stocks or indices based on financial aspects and values on ethics, religiosity, and liquidity aspects. It also showed that SRI-KEHATI is best suited for collecting financial, social, and ethical returns at the same time. We also found out from the Mann-Whitney U test that one of the reasons for SRI-KEHATI's performance was due to the major allocation to the four major banks. There was a significant difference between SRI-KEHATI and the performance of the four banks that have been the stock movers all the way, so investors could select the cherry-picking strategy focusing on those stocks instead. This study has managerial implications for investors and fund managers looking for competitive returns amongst three indices where SRI investment is favorable, targeting higher return and awareness of the higher risk and volatilities. Keywords: equity, liquid, non-parametric, sharia, sustainable responsible investment